(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article aims to analyze the clinical and laboratory course of juvenile psoriatic arthritis (JPA) in children, as well as its local treatment, within the context of Uzbekistan. The study was conducted on 49 pediatric patients with psoriasis who were admitted to the Kashkadarya regional branch of the Republican Specialized Scientific and Practical Medical Center of Dermatovenerology and Cosmetology during the first quarter of 2024-2026. Our study revealed that the development of arthritis often precedes psoriasis and tends to follow a progressive course, particularly in pediatric patients whose clinical diagnosis is delayed. It is necessary for family polyclinic dermatologists and patronage nurses to jointly introduce home examinations and early screening, and to strengthen collaboration between dermatologists and rheumatologists.